2018
DOI: 10.1002/ps.5233
|View full text |Cite
|
Sign up to set email alerts
|

Insect midgut structures and molecules as targets of plant‐derived protease inhibitors and lectins

Abstract: The midgut of insects is involved in digestion, osmoregulation and immunity. Although several defensive strategies are present in this organ, its organization and function may be disturbed by some insecticidal agents, including bioactive proteins like lectins and protease inhibitors (PIs) from plants. PIs interfere with digestion, leading to poor nutrient absorption and decreasing amino acid bioavailability. Intake of PIs can delay development, cause deformities and reduce fertility. Ingestion of PIs may lead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 71 publications
1
46
0
1
Order By: Relevance
“…Insecticidal activity of chitin‐binding lectins has been attributed to their interaction with chitin and glycoconjugates containing N ‐acetylglucosamine residues . The three lectins investigated in this work are chitin‐binding proteins; however, as previously stated, they differ in liquid net charge, molecular mass, and carbohydrate‐binding specificity.…”
Section: Discussionmentioning
confidence: 72%
“…Insecticidal activity of chitin‐binding lectins has been attributed to their interaction with chitin and glycoconjugates containing N ‐acetylglucosamine residues . The three lectins investigated in this work are chitin‐binding proteins; however, as previously stated, they differ in liquid net charge, molecular mass, and carbohydrate‐binding specificity.…”
Section: Discussionmentioning
confidence: 72%
“…The activity of serine proteases in the fifth instar was affected dramatically, leaving a residual activity of 48.2%, corroborating with the results of Oliveira, De Simone, Xavier, and Guedes (). The sub‐subclass of the serine endopeptidases (EC 3.4.21) is known to comprise the main proteases of Lepidoptera (Oliveira et al, ; Srinivasan, Giri, & Gupta, ; Paixao, ; Napoleão et al, ; Pilon et al, ). However, the present study indicated that this relevance occurs strongly only for the fifth instar, the stage of larval development in which enzymatic characterization studies are commonly performed, as they provide a better yield of total proteases.…”
Section: Resultsmentioning
confidence: 99%
“…Lectins have received much attention for their remarkable pesticidal activities and their potential for pest control applications (e.g., insect-resistant transgenic crops) [36][37][38]. In particular, lectins comprise the best available toxins and display a wide array of molecular targets for the control of hemipteran pests [39][40][41].…”
Section: Discussionmentioning
confidence: 99%